The Worship of Shiva in the Context of Local Theology: The Integration of Spirituality and Ecology in Gobleg Village, Bali - I Made Hartaka; Ni Made Yunitha Asri Diantary (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2026)
Amid the escalating global environmental crisis, examining the contribution of local theology to ecological ethics has become increasingly important. This study investigates how the worship of Lord Shiva in Gobleg Village, Bali, constructs an integration between Hindu spirituality and environmental awareness rooted in local wisdom. Employing a qualitative approach with an interpretive ethnographic method, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that the capah ritual structure represents Hindu cosmology, not only reflecting a hierarchy of sacred space but also fostering ecological ethics through the sacralization of nature as a manifestation of the divine. The concept of Shiva as sarvavy?pi (omnipresent) serves as a theological foundation for environmental preservation practices, manifested in the reverence for forests, water sources, and sacred landscapes. This study demonstrates that local Hindu theology in Gobleg Village functions not merely as a form of religious tradition, but as a model of spiritual ecology that is relevant to sustainable development and the strengthening of ecological culture at both local and global levels.